2017
DOI: 10.47672/jsm.150
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Strategies and Performance of Small Scale Agribusiness Firms in Kiambu County

Abstract: Purpose: This study sought to establish the risk management strategies and performance of small agribusiness firms in Kiambu County.Methodology: The study employed descriptive research design. The population of the study was 11,120 small agribusinesses businesses (SME) in Kiambu County. The selection was done in random manner ensuring that all types of firms are considered. This was achieved through stratified random sampling. Data of the list of firms and type was obtained from the County office in-charge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ondiek and Muathe's [16] strategies specified in their study are financial, operational, human resource, regulatory, and disaster risk management strategies, as cited in a study [17]. They claimed that a company's productivity is affected by how it manages these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Ondiek and Muathe's [16] strategies specified in their study are financial, operational, human resource, regulatory, and disaster risk management strategies, as cited in a study [17]. They claimed that a company's productivity is affected by how it manages these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Berry-Stolzle and Xu (2016) shows that risk management can reduce a firm's tax liability, transaction costs of bankruptcy, regulatory costs and mitigate the underinvestment problem in financially constrained firms, thus leading to higher profits. Ondiek and Muathe (2017) used multiple linear regression models to test the significance of the influence of the independent variables on the dependent variable risk management strategies and performance of small agribusiness firms in Kiambu County. The study indicated that financial risk management strategy, operational risk management strategy, human resource risk management strategy, regulatory risk management strategy and disaster risk management strategy affected organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…The study used Value at Risk to measure market risk. Ondiek and Muathe (2017) noted that organization must keep previous records about risks to enable them to forecast future risks. Financial distress affects financial performance of organization therefore keeping informed of various risks reduces the risk of poor performance.…”
Section: Introductionmentioning
confidence: 99%